2011
DOI: 10.1080/10473289.2011.596760
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Combined Measurement and Modeling Method to Quantify Windblown Dust Emissions from the Exposed Playa at Mono Lake, California

Abstract: Particulate matter 10 mm (PM 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Gillette et al, 2004), Sensit probes (e.g. Gillette et al, 1997) and a Tapered Element Oscillating Microbalance (TEOM) PM 10 analyser, Ono et al (2011), working in and around the exposed lake shore of Mono Lake, USA, found that PM 10 emissions varied dramatically with changing surface conditions, an observation consistent with dust emission observations from other playa lake source surfaces (e.g. Reynolds et al, 2007).…”
Section: Monitoring Of Dust Emissions and Dust Flux Measurements Both On And Downwind Of Source Regionssupporting
confidence: 54%
“…Gillette et al, 2004), Sensit probes (e.g. Gillette et al, 1997) and a Tapered Element Oscillating Microbalance (TEOM) PM 10 analyser, Ono et al (2011), working in and around the exposed lake shore of Mono Lake, USA, found that PM 10 emissions varied dramatically with changing surface conditions, an observation consistent with dust emission observations from other playa lake source surfaces (e.g. Reynolds et al, 2007).…”
Section: Monitoring Of Dust Emissions and Dust Flux Measurements Both On And Downwind Of Source Regionssupporting
confidence: 54%
“…Point measurements of sand flux (kg m –2 h –1 ) were made through the array from upwind of the bales to the trailing edge of the array using two types of sand traps: the Cox Sand Catcher (CSC, Ono et al ., ) and the Big Spring Number Eight (BSNE, Fryrear, ) (see supplementary material). Twenty‐four CSCs were placed in six rows of four traps, beginning immediately upwind of the first row of straw bales and then in the center of the lane between straw bale rows 4 and 5; 8 and 9; 12 and 13; 16 and 17; and 18 and 19.…”
Section: Methodsmentioning
confidence: 99%
“…Sand flux was calculated using the approach of Ono et al . () as follows: the mass of sand collected each day in each BSNE trap and CSC trap was divided by the total time that day that the upwind Sensit was recording sand movement to obtain a transport rate in kg m –2 h –1 . The upwind Sensit was used because it was not possible to estimate event duration for traps that were not paired with a Sensit.…”
Section: Methodsmentioning
confidence: 99%
“…Due to limitations on the supply and delivery of dust-sized particles to the atmospheric boundary layer by constraints associated with surface conditions controlling the release of particles [Gillies, 2013], the transport of dust-sized particles will always be below capacity. During extreme dust-storm events, measured concentrations of particles ≤10 μm aerodynamic diameter have exceeded 14,000 μg m À3 (averaged over 24 h) at Mono Lake, CA [Ono et al, 2011], which undoubtedly means that hourly concentration values were potentially much higher. Orlovsky et al [2005] report that during dust storms in Turkmenistan visibility has been reduced to zero, which would require concentration of the suspended material to be much greater than any reported measurements.…”
Section: 1002/2014rg000474mentioning
confidence: 99%